Urgensi Doa Pasca-Pembangunan dalam Perspektif Hadis: Studi Kasus Dermaga Desa Pasir Putih, Pulo Panjang: The Urgency of Post-Construction Prayer from a Hadith Perspective: A Case Study of the Pasir Putih Village Pier, Pulo Panjang - Faroh Rohmatika; Agus Nur Asikin; Mus’idul Millah; Muhammad Alif (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This study aims to analyze the religious practices of the Pasir Putih Village community, Pulo Panjang, especially in the context of the construction of the pier which only began with a prayer reading by a sheikh, without any thanksgiving or joint prayer after the construction was completed. This phenomenon is interesting to study because after the construction was completed, an incident occurred that disturbed the safety of residents, especially children, which gave rise to the assumption of spiritual negligence of the community towards the value of gratitude and blessings of the place. This study uses a qualitative-descriptive approach with field methods and literature studies, and is analyzed through the perspective of the Prophetic hadiths which explain the importance of being grateful for Allah's blessings and maintaining the blessings of the place. Among the hadiths that are the basis is the saying of the Prophet Muhammad SAW: Lā yasykuru Allāha man lā yasykuru an-nās" which means "Not grateful to Allah, people who are not grateful to humans." (HR. Abu Dawud). This hadith is a basis for assessing the importance of expressing gratitude for the blessings of development, including through prayer, alms, or other spiritual activities. The results of the study indicate that the absence of elements of gratitude after development can have an impact on reducing the spiritual awareness of the community, and has the potential to cause disasters as a form of warning. This study recommends that every construction of public facilities in Muslim communities should not only begin with prayer, but also be closed with a form of gratitude that is in accordance with sharia to maintain the value of blessings and social safety of the environment in Pasir Putih, Pulo Panjang.